Efficient Gelation of Graphene Oxide Aqueous Dispersion Induced by Sonication‐Promoted Leuckart Reaction. Issue 11 (19th September 2018) - Song, Man; Tahershamsi, Leili; Zhao, Jie; Zhang, Zhibin; Grennberg, Helena
Abstract: Graphene oxide (GO) undergoes a rapid gelation process in the presence of ammonium hydroxide and formic acid at room temperature which is promoted by ultrasonication. Infrared and X‐ray photoelectron spectroscopy proved partial reduction of GO and nitrogen incorporation, resulting from sonication‐promoted Leuckart reactions at GO carbonyl groups. The amine groups produced via Leuckart reactions undergo further reactions that result in salt bridges with carboxylic groups and covalent cross‐links, both of which contribute to the stabilization of the resulting hydrogel. The resultant GO hydrogel exhibits enhanced thermal stability. Abstract : A reproducible and fast reductive gelation of graphene oxide aqueous dispersion induced by the presence of ammonium hydroxide and formic acid is reported. The studies show that the two additives lead to Leuckart reaction on carbonyl groups on graphene oxide (GO) which results in de‐oxygenation and amination of GO. The produced amines generate various bonds that are responsible for the gelation.